Thermodynamic Properties of the Binary and Ternary Systems Containing N-Formylmorpholine, Methanol, Benzene and Toluene at 298.15 K - Salman, Taghreid A; Shams, Abeer K (Al-Nahrain Journal of Science, 2018)
Excess molar volumes and the deviations in molar refraction of the N-formylmorpholine (NFM) + methanol, methanol+benzene, NFM +benzene, NFM +toluene, methanol + toluene binary systems and also for the ternary systems of NFM + methanol + benzene and NFM + methanol + toluene have been determined at 298.15 K and at atmospheric pressure, by measuring densities and refractive indices over the entire range of composition. These derived data of binary and ternary mixtures were fitted to Redlich–Kister and Cibulka equations for the binary and ternary systems. The ternary data were also compared with the predicted values using the binary contribution models of Tsao-Smith, Kohler and Radojkovicˇ.